Inhibiting Factors Integration of Various Information System in Hospital - Syauqie Muhammad Marier (Association for Scientific Computing Electrical and Engineering, 2018)
Hospitals have diverse information/application systems, such as patient information systems, clinical information systems, laboratory information systems, radiology information systems, pharmaceutical systems, patient registration applications and other information systems. With the implementation of the integration between systems, it will provide the benefits obtained, namely a fast and accurate reporting process, facilitate operational services, establish effective communication between entities, facilitate access to patient information and up-to-date medical knowledge. However, there is still very little integration between information systems within the hospital environment. A study said only 34.78% of hospitals in the Semarang area and 36.62% of hospitals in the Yogyakarta area had already integrated between existing systems. Considering the many benefits obtained from integration, therefore it is necessary to identify the inhibiting factors in the integration process. The method used is to review some of the literature relating to hospital integration in Indonesia. The literature search is done with the Google search engine. The keywords used are the integration of health services and the integration of hospital information systems. The literature chosen is literature that discusses integration in Indonesia, while the literature that discusses the situation outside Indonesia is not included. After getting the literature, then the categorization of the factors that inhibit or cause various information systems in the hospital are not integrated. The results obtained are two factors that most influence the integration process between systems, namely standardization, human resources, leader and finance.